The development and testing of Navy jet fuel (JP-5) surrogates. (1st August 2019) - Cowart, Jim; Foley, Matthew P.; Luning Prak, Dianne
Graphical abstract: Highlights: Navy jet JP-5 surrogates with similar physical but different combustion properties. Surrogate's properties fit military specifications, but derived cetane numbers vary. Low DCN jet fuel surrogates combusted poorly (including startup) in diesel engine. Chemical ignition delay is triple physical ignition delay at high DCNs. Combustion behavior of one surrogate matched representative JP-5 sample. Abstract: In this study five naval jet fuel JP-5 surrogates were developed and tested in comparison to a nominal JP-5 fuel. Because the military uses jet fuel in diesel engines under varied circumstances, the JP-5 fuel surrogates were tested in both the Advanced Engine Technologies Ignition Quality Tester (IQT) and a Yanmar L100W Tier 4 engine. The surrogates were prepared from compounds that represent the classes of components found in JP-5: linear and branched alkanes, aromatic compounds, and cycloalkanes. Five different four-component surrogates containing n -dodecane, 2, 2, 4, 4, 6, 8, 8-heptamethylnonane ( iso -cetane), n -butylbenzene, and n -butylcyclohexane conformed to JP-5 military specifications for flash point, density, viscosity, hydrogen content, aromatic content, and distillation behavior and span a range of reactivities. The flash point of JP-5 is higher than commercial aviation fuel, therefore the surrogates were formulated with higher flashpoint components. The surrogates had very similar physical properties, which compared favorably to those of a base JP-5 fuel. The similar physical properties were chosen to minimize physical spray preparation differences in the various combustion rigs (IQT and Yanmar engine). This result was analyzed directly in the constant volume combustion chamber IQT, in which the analyzed physical delay times were very similar for all the fuels tested. The principle differences between the five surrogates were n -dodecane (high reactivity) and iso -cetane (low reactivity) concentrations, producing derived cetane numbers (DCN) from 34 to 52. Military jet fuel specifications do not limit the value of DCN, so these surrogates could represent qualified jet fuel. The lower cetane surrogates performed poorly in the Yanmar engine. This shows that a qualified jet fuel could fail to combust if used in an emergency diesel generator. One surrogate mixture (Mix-4, mole fractions of 0.25 n -dodecane, 0.20 iso- cetane, 0.15 n -butylbenzene, and 0.40 n -butylcyclohexane) had a DCN of 47, that matched the base JP-5 fuel (DCN = 46.4). In both the steady-state and cold-start engine testing, the Mix-4 surrogate and JP-5 showed very similar combustion behaviors. Thus, it is believed that Mix-4 will function as a strong surrogate for JP-5 performance in other diesel engines as well.